1999
DOI: 10.1097/00005392-199910000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment With Finasteride Daily Does Not Affect Spermatogenesis or Semen Production in Young Men

Abstract: Treatment with 1 mg. finasteride daily for 48 weeks did not affect spermatogenesis or semen production in young men. The effects of 1 mg. finasteride daily on prostate volume and serum PSA in young men without benign prostatic hyperplasia were small and reversible on discontinuation of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
54
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 8 publications
1
54
0
3
Order By: Relevance
“…We hypothesize that perhaps finasteride does not dramatically change the spermatogenesis process in healthy men as shown by Overstreet et al (1999), but in patients with other problems contributing to infertility, the negative influence of finasteride noted by others might be amplified. Future studies should be done to clarify the extent of the effect of finasteride in patients with fertility problems.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…We hypothesize that perhaps finasteride does not dramatically change the spermatogenesis process in healthy men as shown by Overstreet et al (1999), but in patients with other problems contributing to infertility, the negative influence of finasteride noted by others might be amplified. Future studies should be done to clarify the extent of the effect of finasteride in patients with fertility problems.…”
Section: Discussionmentioning
confidence: 87%
“…9 However, Overstreet et al (1999) reported that finasteride 1 mg/day did not affect spermatogenesis, seminal production, sperm motility, or sperm morphology in young healthy men. 1 The 3 patients reported on this paper showed abnormal sperm concentration and motility while using finasteride 1 mg/day. Those alterations were completely reversed (patient 1 and 2) or improved (patient 3) 3 or 4 months after the interruption of finasteride treatment.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations